2016
DOI: 10.1007/s12671-016-0649-y
|View full text |Cite
|
Sign up to set email alerts
|

Creativity Is Enhanced by Long-Term Mindfulness Training and Is Negatively Correlated with Trait Default-Mode-Related Low-Gamma Inter-Hemispheric Connectivity

Abstract: It is becoming increasingly accepted that creative performance, especially divergent thinking, may depend on reduced activity within the default mode network (DMN), related to mind-wandering and autobiographic selfreferential processing. However, the relationship between trait (resting-state) DMN activity and divergent thinking is controversial. Here, we test the relationship between resting-state DMN activity and divergent thinking in a group of mindfulness meditation practitioners. We build on our two previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 89 publications
(100 reference statements)
3
25
0
Order By: Relevance
“…Asceticism advocated by Buddhism devalues materialism and productivity growth ( Westwood and Low, 2003 ). This may counteract the positive effects of Buddhist practice such as mindfulness ( Berkovich-Ohana et al, 2017 ) and meditation ( Colzato et al, 2012 ; Ding et al, 2014 ) on creativity. However, the effects of Buddhism on creativity need deep investigations in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asceticism advocated by Buddhism devalues materialism and productivity growth ( Westwood and Low, 2003 ). This may counteract the positive effects of Buddhist practice such as mindfulness ( Berkovich-Ohana et al, 2017 ) and meditation ( Colzato et al, 2012 ; Ding et al, 2014 ) on creativity. However, the effects of Buddhism on creativity need deep investigations in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, Buddhism may “de-emphasize materialism and encourage acceptance and quietude” ( Westwood and Low, 2003 , p. 242), suggesting that Buddhism does not encourage change and innovation. On the other hand, Buddhism emphasizes impermanence and recommends its adherents to engage in mindfulness and meditation practice, which can improve creativity ( Colzato et al, 2012 ; Ding et al, 2014 ; Berkovich-Ohana et al, 2017 ). These effects of Buddhism may operate in the opposite directions, leading us to hypothesize that there is no relationship between Buddhism culture and national creativity ( Hypothesis 2d ).…”
Section: Introductionmentioning
confidence: 99%
“…Common styles of meditation include focused attention meditation (FA)—which requires sustaining one's attention on a particular object or sensation such as the breath—, open monitoring meditation (OM)—which involves a non-judgmental, non-selective awareness of the present moment—, loving-kindness and compassion meditation (LK)—which involves the cultivation of compassion toward oneself and others—, and mantra recitation (MR)—which involves the repetition of a sound, word or sentence (see Box 1). The subjective effects of meditation are multifaceted, including enhanced attention and sensory processing (Brown, 1977 ; Jha et al, 2007 ), largely positive emotions and mood (Ortner et al, 2007 ; Davidson and Lutz, 2008 ; Lutz et al, 2008 ), increased cognitive flexibility and creativity (Horan, 2009 ; Capurso et al, 2014 ; Ding et al, 2014 ; Berkovich-Ohana et al, 2017 ), and, in some cases (usually with increasing expertise) dramatic disruptions of one's sense of self (Austin, 2006 ; Dorjee, 2016 ; Berkovich-Ohana and Wittmann, 2017 ).…”
Section: The Neuroscience Of Meditation and Psychedelics: An Overviewmentioning
confidence: 99%
“… 10 FA 13 can promote positive changes in the key neural signals (frontal theta inter-trial coherence and parietal P3b latency) of attention networks. Furthermore, meditation also attenuates activity of the default mode network (DMN), 14 with dysfunction of the DMN subsystem in the anterior (medial prefrontal cortex) and posterior (cingulate cortex) following a larger number of long-term meditations. 15 16 Our study 17 observed reduced DMN activity in monks following persistent meditation practice and reconstruction of the large-scale network of EEG gamma waves as well as theta waves by meditation.…”
Section: Biological Mechanisms Of Meditationmentioning
confidence: 99%